2022
DOI: 10.1021/acs.biomac.2c01031
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembly and Small-Molecule Binding by Protein-Engineered Coiled-Coil Fibers

Abstract: The ability to engineer a solvent-exposed surface of self-assembling coiled coils allows one to achieve a higher-order hierarchical assembly such as nano-or microfibers. Currently, these materials are being developed for a range of biomedical applications, including drug delivery systems; however, ways to mechanistically optimize the coiled-coil structure for drug binding are yet to be explored. Our laboratory has previously leveraged the functional properties of the naturally occurring cartilage oligomeric ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(71 citation statements)
references
References 41 publications
9
62
0
Order By: Relevance
“…27 We have also recently shown that Q2 and Q dock CCM similarly by in silico models using Rosetta where Q2 and Q possess interface scores of −46.3 kcal mol −1 and −46.2 kcal mol −1 , respectively. 35 The similar ATR-FTIR and behavior of CCM-bound Q2 shown here further confirm that CCM exhibits a positive interaction inside the hydrophobic pore of the coiled-coil eliciting an increase in α-helicity and stability.…”
Section: Secondary Structural Changes Upon Gelationsupporting
confidence: 76%
See 1 more Smart Citation
“…27 We have also recently shown that Q2 and Q dock CCM similarly by in silico models using Rosetta where Q2 and Q possess interface scores of −46.3 kcal mol −1 and −46.2 kcal mol −1 , respectively. 35 The similar ATR-FTIR and behavior of CCM-bound Q2 shown here further confirm that CCM exhibits a positive interaction inside the hydrophobic pore of the coiled-coil eliciting an increase in α-helicity and stability.…”
Section: Secondary Structural Changes Upon Gelationsupporting
confidence: 76%
“…Design Q2 was previously designed 35 to assemble into thinner nanofibers relative to Q by reduced lateral supramolecular assembly (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, similar drug binding studies have been completed with the hydrophobic small molecule, curcumin (CCM). 15 CCM is known to induce fiber thickening in collagen and Q. 14,16,17 We hypothesize that a similar mechanism occurs between AzoCholine and Q where binding of AzoCholine causes exposure of nonpolar groups and increased surface activity in Q, which further drives its fiber aggregation.…”
Section: Resultsmentioning
confidence: 98%
“…[1a, 17] Alpha-helical coiled-coil peptides have been shown to be particularly useful, [18] and have been utilized to generate nanofibrillar assemblies by modulating the solvent-exposed surface of the coiled-coils. [19] Recently, the Saven group has computationally designed peptides to form antiparallel, tetrameric coiled coils, or "bundlemers", with dimensions corresponding to a nanoscopic cylinder of 2 nm × 4 nm; [20] these sequences have been produced by both solid-phase and recombinant methods. [20a, 21] While unmodified bundlemers are unable to assemble into long 1D fibrils alone, [22] covalent reaction of bundlemers with complementary functional groups yields bundlemer polymers with extreme chain stiffness and contour lengths of a few micrometers, [20a] establishing these coiled coil-forming peptides as excellent building blocks for creating programmable, peptide-based, and structurally robust 1D and 2D nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, short self‐assembling peptides from structural proteins have been widely employed in the generation of assembled materials for use as drug carriers, gene‐targeting therapeutics, templating of inorganic molecules, and fabrication of structured materials [1a, 17] . Alpha‐helical coiled‐coil peptides have been shown to be particularly useful, [18] and have been utilized to generate nanofibrillar assemblies by modulating the solvent‐exposed surface of the coiled‐coils [19] . Recently, the Saven group has computationally designed peptides to form antiparallel, tetrameric coiled coils, or “bundlemers”, with dimensions corresponding to a nanoscopic cylinder of 2 nm×4 nm; [20] these sequences have been produced by both solid‐phase and recombinant methods [20a, 21] .…”
Section: Introductionmentioning
confidence: 99%